Transportation System of Major Cities in the Middle East - Kasza, Bianka; Ungvárai, Ádám; Lipták-Váradi, Julianna (International Journal of Engineering and Management Sciences, 2017)
The quality of transportation has a great effect on the quality of our everyday life and the future of our planet. In contrary to Europe, transportation culture of the big cities in the Middle East region has grown fully different way. These Middle Eastern cities tend to have a different historical, traditional and structural background compared to other cities all around the world. One of these big cities is in the focus of our paper: Rijad, with 6 million inhabitants is the archetypal car dominated city of the Arabic world. We also elaborated a comparison to 4 other cities: Dubai as a city similar to Rijad, Amsterdam as a city with a modern green attitude, Budapest as a metropolitan city in Hungary and last but not least Debrecen which is a Hungarian city with moderate population. As a lesson learnt, we try to give some possibilities and outlooks for Rijad, in order to improve the structure of transportation.